An ab initio quantum dynamical analysis of the vibronic structure of the X2Bg photoelectron spectral band of s-trans-1, 3-butadiene - Nikoobakht, Behnam; Dreuw, Andreas; Köppel, Horst (Chemical physics, 2018)
The nuclear dynamics of the s-trans-1,3-butadiene cation following a fast ionization process is studied theoretically for the first time, using a fully quantal approach. The three lowest coupled X2Bg,A2Au and B2Ag states are taken into account and up to six nuclear degrees of freedom, including out-of-plane dihedral angles, are included. The underlying potential energy surfaces have been computed at RS2C level, a CASPT2 variant, and widely different CAS spaces have been evaluated beforehand. In the dynamics simulation, a small population transfer from the X2Bg to the A2Au and B2Ag states has been observed on a time scale 30-40fs. The vibronic structure of the first band of the simulated photoelectron spectrum is in very good agreement with the experimental one. Our calculation reveals the vibrational mode corresponding to the symmetric stretching of the terminal CC bond to dominate the vibrational progression of the first band of the photoelectron spectrum of s-trans-1,3-butadiene.